서울 양재동 화훼공판장 시설현대화 방안 - 김병률 (한국농촌경제연구원, 2010)
Yang-jae Flower Joint Market (YFJM) which opened in 1991 shows an increasing trend in its transaction volume. However, Yangjae market's equipments has been time-worn and thereby the distribution efficiency has been reduced. Furthermore, the site for the storage and distribution is overcrowded. Because Seo-cho Gu, the sub-district of Seoul, has a plan to move away the Gangnam Express Bus Terminal(GEBT), a flower whole sale market which has been located in the GEBT needs to be transferred. Auction Market for Orchid(SAMO) in Seong-nam City is also going to be transferred. Therefore the YFJM is requested to absorb the function of the whole sale market of the GEBT and also the middlemen who played key roles in SAMO. Becaue these will make the YFJM the biggest flower wholesale market in Korea, the YFJM needs to be properly prepared for the new status. For example, as in flower wholesale markets in Netherland and Japan, the YFJM needs to be well equipped with advanced marketing system for flowers through renewing or modernizing the facilities of auction, distribution, and storage. This study suggests the needs of rebuilding the facilities of the YFJM. The mordernization should be progressed in a direction toward representing and boosting the Korean flower industry. For this purpose, this study also made an economic analysis on the effect of the YFJM facilities rebuilding.